2021
DOI: 10.1177/03611981211005774
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Artificial Neural Network-Based Procedure for the Verification of Traffic Speed Deflectometer Measurements

Abstract: Since the 1980s, the falling weight deflectometer (FWD) has been the primary deflection-measuring device in the United States to evaluate the structural conditions of in-service pavements. However, the stop and go nature of the FWD limits its application at the network level. In the early 2000s, the traffic speed deflectometer (TSD) was introduced as an alternate deflection-measuring device for network-level applications. TSD collects deflection measurements while traveling at traffic speed, which provides imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Research by Li et al [7] showed that the TSD had a high correlation with BBD measurements, satisfying the requirements of road network-level deflection measurement. Liao et al [1] and Abohamer et al [2] declared that the correlation coefficients of TSD and FWD measurements reached 0.945 and 0.972, respectively. Nielsen et al [10] concluded that the FWD and TSD measurements, although similar, were not equivalent, and their details differed.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research by Li et al [7] showed that the TSD had a high correlation with BBD measurements, satisfying the requirements of road network-level deflection measurement. Liao et al [1] and Abohamer et al [2] declared that the correlation coefficients of TSD and FWD measurements reached 0.945 and 0.972, respectively. Nielsen et al [10] concluded that the FWD and TSD measurements, although similar, were not equivalent, and their details differed.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, instruments such as the Benkelman Beam Deflectometer (BBD) and the Falling Weight Deflectometer (FWD) were used to measure it. However, such instruments need to stop for 1-2 minutes during each test and suffer from poor safety and low efficiency [2], [3]. Currently, the focus of researchers has gradually shifted to high-speed, continuous, and non-destructive measurements [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations